Латинська Америка в дослідженнях російських етнографів за останні тридцять років - Александренков, Е. (Народна творчість та етнографія, 2010)
Статья посвящена истории исследований в области латиноамериканистики российскими и советскими учёными на примере научной деятельности сотрудников Института этнографии им. Н. Н. Миклухо-Маклая АН СССР (московское и ленинградское отделения). The article is dedicated to the Latin American researches provided by the Russian and Soviet scientists illustrated with the scientific activities of the representatives of the Soviet Academy of Science’s Myklukho-Maklai Ethnographical Institute (Moscow and Leningrad branches).